Podobe turizma - Brezovec, Aleksandra (Družboslovne razprave, 2012)
This article discusses the image-formation process in tourism using a communication concept. Tourism images are based on information, symbols and codes that only become meaningful in the interaction of participants in the communication process. Focus group interviews and the photoelicitation technique were used to study how messages and participants mutually create meanings in tourism. The research results show that communication in tourism is not limited to individuals but also includes social groups that reinforce their social group status through communication in tourism.
Keywords: Tourism; Turizem; Communication; Komuniciranje; Slovenia; Slovenija; tržno komuniciranje